„Oścień śmierci” według Edyty Stein - Grzegorczyk, Anna (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
Edith Stein’s ideas about an experience of death are reconstructed by using the parallel method, i.e. in comparison with the ideas of K. Jaspers, P. Ricoeur and U. Eco. The adoption of this method allows one to explore Edith Stein’s both philosophical and existential radicalism or to systematize philosophers’ convictions concerning a limit-experience, i.e. death. The experience of the Mystery of the Cross, which is equivalent to the experience of death, appears in E. Stein’s texts as the philosophers’ stone related to human experience. However, the verbalization of this experience as the “science of the Cross” and a “holy science” is at the same time the highest form of human knowledge.